Hunting for the library value: Benchmarking as a communication tool (Journal of EAHIL, 2019)
International cooperation is an essential part of library and information professionals' work. Three European health and medical libraries started a benchmarking project in year 2013, aiming at comparing services among our libraries in order to find and implement best practices. We wanted to share ideas, solutions and examples. The purpose of this paper is to give the final report of the five-year benchmarking project. The project was a continuous best-practice benchmarking process. At the end the process, we essentially experienced this kind of library benchmarking as a communication and development tool. International benchmarking provides new skills for information professionals